Studying the antibacterial effect of group of essential oils against clinically isolated MDR strains (Journal of Hama University, 2025)
Abstract : Aim of the study: The increasing of antibiotic resistance cases has become a serious problem threats public health and continuously spread worldwide rendering the previously effective antibiotic inactive. Also, the antibiotic resistance phenomenon considered as a main responsible for the therapeutic failure in the recently bacterial infection treatments. Therefore, there is an urgent need to find alternative treatments which may be promising to eradicate resistance cases or increasing the activity of antibiotic recently being used.Material and methods: Essential oil extraction using steam distillation methods for the aerial parts of the following plants (Thymus syriacus, Rosmarinus officinalis, Cinnamomum zeylanicum ,Syzygium aromaticum). The antibacterial activity of these essential oils was evaluated against clinically isolated multi-drug resistant strains (  Klebsiella pneumonia , Pseudomonsa aeruginos, Streptococcus pneumonia ) by using disk diffusion methods.Result: The results showed that Thymus syriacus and Syzygium aromaticum essential oil had the strongest activity as antibacterial against bacterial strains being studied at 25% concentration. While Rosmarinus officinalis essential oil showed lower activity at 25% concentration. While Cinnamomum zeylanicum essential oil showed no activity at the same concentration.Conclusions: Some essential oil have a significant effect against multi - drug resistant bacteria and could be considered as alternative promising therapy against bacterial infection. More studied are needed to evaluate the essential oil activity against other microorganisms and determination the effective concentration of these essential oils, studying its toxicity and its activity in vivo .
Keywords: Essential oils, antibacterial activity, resistant strains,